The Relationship of Legal Resources with Human Civilization in Indonesia Legal History Perspective - Bima Wahyu Bintoro; Wardah Yuspin (Proceeding International Conference Restructuring and Transforming Law, 2022)
Human civilization continues to develop following the civilization of its era, the transition period from pre-history, the working period to the modern era today. The transition to human civilization provides an accumulation of information about the substance of the law in force at that time. History is horizontal in time, which makes it a reflection of the civilizations listed in historical relics, including legal civilization. History has the function of explaining and explaining something that happened in the past, giving a fundamental role to the science of history. So as to be able to explain events in the past to reflect human knowledge in the future.This type of research uses normative research methods. The normative research method is called legal research which focuses on doctrinal emphasis on secondary data, namely legal material that has been documented. Legal history has an important role in studying legal science as an object, has an important role in explaining and explaining the strategy of legal concepts in the past. Historical awareness for historians academics in general or legal historians is able to work together in studying legal science in the past, so that they are able to interpret and interpret humans in the present, to provide benefits and certainty for the guidelines of human life itself.